El PROMEP en la Universidad de Guanajuato: Balance e Impacto, Periodo 1997- 2008 - Martínez, Patricia Catalina; Preciado Tarabay, Salma; Rico Venegas, Rosa María (Acta Universitaria, 2008)
National policies on Higher Education have had a high level of consistency and continuityin their central purposes: coverage, quality, relevance, diversifi cation, decentralization,equity, management, planning, evaluation and coordination. Based on this contention, theUniversity of Guanajuato is searching for new strategies that meet institutional goals andwhich may also adapt to local conditions. To reach these goals, the University has appealedto a teacher development program (Programa de Mejoramiento del Profesorado, PROMEP), established by the Secretariat of Education (SEP). This program has been, without a doubt, an important factor in the improvement of institutional quality indicators as the growing number of teachers with PROMEP profile shows, the program has also supported the consolidation of academic groups and the empowerment of its members contributing to 82.15% of teachers with a degree. Accomplishments as a result of PROMEP since its inception in 1996 until 2007 have been substantial. However, it is important to mention that the support academics got was based on their personal needs as well as those of the academic groups where they belong, their departments and the DES.
Keywords: Array; Array; Array